Analisis Hukum Tindak Pidana Pelaku Pencabulan Anak Dibawah Umur di Depok Berdasarkan Perspektif UU Perlindungan Anak (Studi Kasus Putusan Nomor 27/Pid. Sus/2024/PN Dpk) - Latifah Kholifah Arief; Bintang Wicaksono (IBLAM Law Review)
The legal protection that has been provided by the government in cases of child abuse is by passing various regulations governing the imposition of sanctions and fines as well as fulfilling the rights of victims and perpetrators, this is stated in the Child Protection Law, the Sexual Violence Law, the Old and New Criminal Code. From these regulations, the protection provided for children as victims of sexual abuse is providing restitution and compensation for the losses experienced by the victim, providing psychological guidance for the victim, providing medical services, and the victim receiving legal protection, especially when being a witness to the case they are experiencing. And in its implementation in the case of decision Number 27/Pid.Sus/2024/PN.Dpk based on the author's study using normative legal research methods based on existing data sources, that in this case the law used in imposing criminal sanctions and fines was based on Law No. 35 of 2014 concerning Amendments to Law no. 23 of 2002 concerning Child Protection, by fulfilling the elements in article 76E by committing deception so that obscene acts can be committed against children, and criminal sanctions and fines are regulated in article 82, namely imprisonment for a minimum of 5 (five) years and a maximum of 15 (fifteen) years and a maximum fine of Rp. 5,000,000,000.00 (five billion rupiah) in this case the perpetrator committed repeated criminal acts which fulfilled the elements of Article 64 Paragraph 1 of the Criminal Code.